Unit Template Synchronous Reference Frame Theory Based Control Algorithm for DSTATCOM - Bangarraju, J.; Rajagopal, V.; Jayalaxmi, A. (Journal of the Institution of Engineers (India). Series B, Electrical Engineering, Electronics and telecommunication engineering, Computer engineering, 2014)
This article proposes new and simplified unit templates instead of standard phase locked loop (PLL) for Synchronous Reference Frame Theory Control Algorithm (SRFT). The extraction of synchronizing components (sinθ and cosθ) for parks and inverse parks transformation using standard PLL takes more execution time. This execution time in control algorithm delays the extraction of reference source current generation. The standard PLL not only takes more execution time but also increases the reactive power burden on the Distributed Static Compensator (DSTATCOM). This work proposes a unit template based SRFT control algorithm for four-leg insulated gate bipolar transistor based voltage source converter for DSTATCOM in distribution systems. This will reduce the execution time and reactive power burden on the DSTATCOM. The proposed DSTATCOM suppress harmonics, regulates the terminal voltage along with neutral current compensation. The DSTATCOM in distribution systems with proposed control algorithm is modeled and simulated using MATLAB using SIMULINK and Simpower systems toolboxes.